(untitled) (Human Factors in Design, 2018)
A usability inspection is an evaluation method carried out by one or more experts in HCI, individuals with solid theoretical and practical foundations for the formal and objective observation of a product. One of the most used methods is the heuristic evaluation, a term coined by Jakob Nielsen in 1989 that consists of using a set of usability heuristics to examine a product and analyze its degree of compliance. Due to the ever-growing use of Facebook by older adults, a heuristic evaluation of this application is carried out in this article, where principles of usability have been adapted to fit the profile of an older adult and the interaction with collaborative aspects and groupware functions that are characteristic of social networks. The results of this process of inspection will be of utmost importance to understand whether the current applications consider the older adult as a possible user, respecting principles of usability consistent with their profile.